Influence of folding mechanism of bicycles on their usability. (May 2018) - Roh, Jongryun; Hyeong, Joonho; Kim, Sayup
Abstract: In this study, foldable bicycles were evaluated in terms of their usability. Four types of folding mechanisms were identified depending on the number of pivots and the pivot axis direction: single lateral pivot (SLP), single vertical pivot, dual lateral pivot, and combined vertical–lateral pivot. Next, four bicycles—one each of these four types—were selected as test specimens. Ten subjects performed folding and unfolding tasks on each of these bicycles, and three-dimensional body motions and ground reaction forces were measured. The maximum trunk flexion angles and maximum increments in the ground reaction force were used as governing parameters for evaluating the comfort level for each bicycle type. The SLP type provided the lowest upper body flexion and ground reaction force and was hence judged to be the most comfortable folding system. Hence, a promising type of easily foldable bicycle was proposed, thereby encouraging its incorporation into public transit systems. Highlights: Foldable bicycle mechanisms were identified depending on the number of pivots and the direction of the pivot axis. Folding mechanisms of bicycles were evaluated in terms of their usability. Three-dimensional body motion and the GRF were measured to evaluate folding usability for four foldable bicycle types. The SLP type provided the lowest body flexion and GRF and was hence judged to be the most comfortable folding system.